1990
DOI: 10.1182/blood.v75.2.329.329
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of thrombomodulin: a natural anticoagulant

Abstract: NDOTHELIAL CELLS lining blood vessels possess E anticoagulant functions, although they can rapidly become procoagulant when injured. The anticoagulant actions include production of prostacyclin,' secretion of plasminogen activator,* cell surface heparin containing proteogly- From the Division of Hematology/Oncology. Washington Univer-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…Cytokines, such as IL-1 and TNF-a, cause endothelial and monocyte activation resulting in a switch from an anticoagulant to a prothrombotic phenotype by (for example) downregulation of thrombomodulin (Dittman & Majerus, 1990) and upregulation of TF (Khan et al, 2010). IL-1b and TNF-a are produced by APML cells (Griffin et al, 1987).…”
Section: The Contribution Of Inflammatory Cytokinesmentioning
confidence: 99%
“…Cytokines, such as IL-1 and TNF-a, cause endothelial and monocyte activation resulting in a switch from an anticoagulant to a prothrombotic phenotype by (for example) downregulation of thrombomodulin (Dittman & Majerus, 1990) and upregulation of TF (Khan et al, 2010). IL-1b and TNF-a are produced by APML cells (Griffin et al, 1987).…”
Section: The Contribution Of Inflammatory Cytokinesmentioning
confidence: 99%
“…Therefore, it is a striking observation that IE CSA are only present at high levels during pregnancy and that anti-IE CSA antibodies are largely restricted to pregnant women. Indeed, CSA is expressed throughout the surface of endothelial cells in the microvasculature of other target organs, such as the brain and the lung (Dittman and Majerus, 1990; Wong et al 1991). Furthermore, it has been demonstrated that IE CSA cytoadhere to monkey brain microvascular endothelial cells and human lung epithelial cells, apparently expressing chondroitin sulfate (Robert et al 1995; Traore et al 2000).…”
Section: Selection Mechanismmentioning
confidence: 99%
“…Free a-thrombin triggers platelet clotting, generates fibrin and active factor XIII to stabilize the clot and activates clotting factors V, VIII and XI, which in turn generate more o~-thrombin (Fenton, 1986;Davie et al, 1991, and references therein). In contrast, a-thrombin bound to thrombomodulin decelerates clotting by preferentially activating protein C, which then proteolytically inactivates factors Va and Villa in the clotting cascade leading to thrombin (Esmon, 1987;Dittman & Majerus, 1990). Thrombin also triggers the inflammation response to vascular damage by activating neutrophils and monocytes (reviewed by Coughlin, 1994).…”
Section: Introductionmentioning
confidence: 99%